Toward improving energy security in Kenya via HTLS conductors and load balancing - Mkabane, C. C. (Strathmore University, 2024)
The Industrial and Commercial sectors of the economy are rapidly growing and hence, energy consumption and transmission line loading are also increasing. This explains the major breakdowns related to transmission lines since the initially installed lines are not able to handle the increased energy requirements. Previous studies have been done replacing ACSR with ACCC conductors to reduce thermal line losses. The project aims to replace ACSR with ACCC conductors in short lines, analyze the length of the line in which the ACCC conductor will cease to be beneficial, and analyze the mechanical properties of the line. The Kenyan grid will be analyzed in its present state by performing a load flow analysis and a sag and tension analysis. The short lines will then be replaced by ACCC conductors and the load flow and sag and tension analysis of the new system done. The two systems will then be compared. The length of the line in which the ACCC conductor will no longer be beneficial for application will be determined. The analysis will be performed using Power Factory DigSilent software.
Full - text thesis